2009
DOI: 10.1111/j.1442-200x.2008.02757.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive smoking on growth and infection rates of breast‐fed and non‐breast‐fed infants

Abstract: Tobacco smoke exposure of infants has negative consequences on growth, otitis media, and upper and lower respiratory tract infections. Breast-feeding promoted the growth of infants who were passively exposed to tobacco smoke and protected them against infections. Smoking should not be permitted in households with infants. When this is impossible, breast-feeding should be promoted to protect the infants against the health hazards of passive smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
0
16
0
2
Order By: Relevance
“…Approximately 40% of children worldwide are exposed to cigarette smoke at home, and 43% have at least one parent who smokes (World Health Organization (WHO), 2009). This early exposure to constituents of cigarette smoke makes children susceptible to respiratory infections, ear infections, growth retardation, and an increased frequency of hospitalizations due to infections (Ladomenou et al, 2009; Yilmaz et al, 2009a). Moreover, these children have decreased serum antioxidant vitamins (A, C, and E), which can contribute to an oxy-cellular redox imbalance and, consequently, increased lipid peroxidation and protein and DNA damage by free radicals present in cigarette smoke (Yilmaz et al, 2009b).…”
Section: Worldwide Tobacco Consumptionmentioning
confidence: 99%
“…Approximately 40% of children worldwide are exposed to cigarette smoke at home, and 43% have at least one parent who smokes (World Health Organization (WHO), 2009). This early exposure to constituents of cigarette smoke makes children susceptible to respiratory infections, ear infections, growth retardation, and an increased frequency of hospitalizations due to infections (Ladomenou et al, 2009; Yilmaz et al, 2009a). Moreover, these children have decreased serum antioxidant vitamins (A, C, and E), which can contribute to an oxy-cellular redox imbalance and, consequently, increased lipid peroxidation and protein and DNA damage by free radicals present in cigarette smoke (Yilmaz et al, 2009b).…”
Section: Worldwide Tobacco Consumptionmentioning
confidence: 99%
“…103 Smoking should not occur in the presence of the infant so as to minimize the negative effect of secondary passive smoke inhalation. 104 Smoking is also a risk factor for low milk supply and poor weight gain. 105,106 MATERNAL DIET Well-nourished lactating mothers have an increased daily energy need of 450 to 500 kcal/day that can be met by a modest increase in a normally balanced varied diet.…”
Section: Contraindications To Breastfeedingmentioning
confidence: 99%
“…Lower rates of obesity are linked to breastfeeding, which has a protective affect against obesity in later life ( 26 ). Yilmaz et al ( 27 ) found that breastfeeding promoted the growth of infants who were passively exposed to tobacco smoke and it is advised that breastfeeding should be promoted to protect infants against the health hazards of passive smoking. It primarily protects against obesity and secondarily prevents cardiopulmonary complications in obese patients.…”
Section: Discussionmentioning
confidence: 99%